Urocortin 2 in cardiovascular health and disease. Issue 7 (July 2015) - Adão, Rui; Santos-Ribeiro, Diana; Rademaker, Miriam T.; Leite-Moreira, Adelino F.; Brás-Silva, Carmen
Highlights Urocortin (Ucn)-2 regulates cardiac function. Ucn-2/CRH-R2 system activation promotes a consistent relaxation of the vessels. Animal studies have shown beneficial therapeutic effects of Ucn-2 in heart failure. Therapeutic benefits of Ucn-2 have also been shown in patients with heart failure. Ucn-2 is emerging as a promising therapeutic option for cardiovascular diseases.